J.E.N.T Enterprise - Jikon, J.Denwnner Alvion; Azlyzan, Nurul Afifah T; Jasni, Nony Hayatie; Jumpaan, Siti Nadia (2016)
Stevia leaves is the one of the way for controlling the sugar taken in our daily life. If the human body receive a lot of glucose and conventional sugar it will harm the human body by get a chronic disease such as diabetic disease. People who has the diabetic diseases need to consume a lot of medicines to help them much better. J.E.N.T enterprise is a company that produce a Univia product from the combination of milk and 2% of stevia powder for the diabetic people age 45 until 80 years old. Univia can be consumed twice a day by the diabetic people. It help to give an energy and planning a healthy diet for them. Our company was located at Metro town, Kolombong as we are targeting the diabetic people around Sabah. Univia product was allocate at clinic, hospital and pharmacy. 1 unit of the Univia product is RM200.00. Other than that, the strength of our company's product used less of the conventional sugar and only used the naturally one extracted from the leaves.